Social determinants of health and maxillofacial injuries in children and adolescents victims of violence: A novel GIS‐based modelling application. Issue 3 (18th January 2019) - de Macedo Bernardino, Ítalo; da Nóbrega, Lorena Marques; da Silva, José Régis Cordeiro; de Alencar, Catarina Ribeiro Barros; de Olinda, Ricardo Alves; d'Ávila, Sérgio
Abstract : Background: Physical violence against children and adolescents comprises a serious public health problem and often results in oral and maxillofacial traumas. Social determinants may favour the occurrence of these events, but few studies have critically evaluated the interaction between social and geographical risk factors. Aims: To investigate the spatiotemporal distribution of oral and maxillofacial traumas resulting from violence against children and adolescents through geostatistical techniques. Methods: This study was an ecological analysis of cases of trauma caused by violence against Brazilian children and adolescents using aggregated data from victims attended at a Center of Forensic Medicine and Forensic Dentistry between January 2012 and December 2015. Data were analysed through modelling based on geographic information system (GIS). Results: Two distinct patterns of longitudinal trajectory of oral and maxillofacial trauma related to violence against children and adolescents were identified (TP1 and TP2, P  < 0.05). The spatial regression analysis revealed a statistically significant association between higher incidence of cases and areas with worse socioeconomic conditions (β = 0.047, SE = 0.020, P  < 0.05). Conclusion: Neighbourhoods with considerable socio‐spatial vulnerability for violence against children and adolescents and maxillofacial traumas were identified.